Hollow Nanostructures of Molybdenum Sulfides for Electrochemical Energy Storage and Conversion. Issue 1 (16th December 2016) - Yu, Xin‐Yao; Yu, Le; Lou, Xiong Wen (David)
Abstract : Hollow nanostructures of molybdenum sulfides (MoS x, x = 2 or 3) hold great promise as electrode materials for various energy‐related systems owing to their attractive electrochemical properties. Recent advances in the synthesis of hollow MoS x nanostructures with tailored morphology and composition are introduced, along with their applications in electrochemical energy storage and conversion, including lithium‐ion batteries and the electrocatalytic hydrogen‐evolution reaction. The importance of structural and compositional engineering on the electrochemical performance of hollow MoS x nanostructures is highlighted. Specifically, bare hollow MoS x structures, including hollow spheres and hollow polyhedral nanostructures, hollow MoS x –carbon composite structures, and hollow transition‐metal‐incorporated MoS x structures are discussed. Finally, a perspective is provided on current challenges and future research directions in this area. Abstract : Hollow nanostructures of molybdenum sulfides are promising electrode materials for lithium‐ion batteries and electrocatalysts for the hydrogen evolution reaction. The recent progress in the synthesis of high‐quality hollow nanostructures of molybdenum sulfides is highlighted. Particular emphasis is on structural and compositional engineering and their effects on electrochemical performance.